2014
DOI: 10.1289/ehp.1307459
|View full text |Cite
|
Sign up to set email alerts
|

GSTP1 and TNF Gene Variants and Associations between Air Pollution and Incident Childhood Asthma: The Traffic, Asthma and Genetics (TAG) Study

Abstract: Background: Genetics may partially explain observed heterogeneity in associations between traffic-related air pollution and incident asthma.Objective: Our aim was to investigate the impact of gene variants associated with oxidative stress and inflammation on associations between air pollution and incident childhood asthma.Methods: Traffic-related air pollution, asthma, wheeze, gene variant, and potential confounder data were pooled across six birth cohorts. Parents reported physician-diagnosed asthma and wheez… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 51 publications
2
64
0
2
Order By: Relevance
“…Because of these differences, we did not perform meta-analysis of the interaction bs, but we did present interaction bs and P values for each data set. Previous G 3 E interaction analyses using candidate gene approaches suggested that genes related to antioxidative stress systems, inflammation, and innate immunity (e.g., GSTP1, TNF and TLR2/4) are important effect modifiers (12,13). These genes were not among the top hits in our GWIS, but this did not exclude true interaction effects for key SNPs as previously reported.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Because of these differences, we did not perform meta-analysis of the interaction bs, but we did present interaction bs and P values for each data set. Previous G 3 E interaction analyses using candidate gene approaches suggested that genes related to antioxidative stress systems, inflammation, and innate immunity (e.g., GSTP1, TNF and TLR2/4) are important effect modifiers (12,13). These genes were not among the top hits in our GWIS, but this did not exclude true interaction effects for key SNPs as previously reported.…”
Section: Discussionmentioning
confidence: 59%
“…Oxidative stress and inflammation represent pathogenic pathways involved in asthma development (3). Interactions between air pollution and allele variants in genes related to antioxidative stress systems, inflammation, and innate immunity have been reported in relation to the incidence of asthma (12,13). Such gene-environment (G 3 E) interactions may partially explain the inconsistencies between air pollution and the incidence of asthma.…”
Section: At a Glance Commentarymentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 shows the flow of papers. A total of 42 studies met our inclusion criteria [31,32,33,34,36,37,38,39,40,41,42,43,44,45,46,47,48,50,51,52,58,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87] (Table 1). …”
Section: Resultsmentioning
confidence: 99%
“…Where necessary, data items were missing from the main papers, data was extracted from the supplementary materials [31,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52], and the associated publications [53,54,55,56,57,58,59,60,61,62,63,64,65,66]. Data extraction was undertaken manually by one researcher (Haneen Khreis).…”
Section: Methodsmentioning
confidence: 99%